Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Consider the following integral (originating from the product of the Laplace transforms of $f$ and $g$):

$$\int_0^\infty \int_0^\infty f(u)\ g(v) e^{-s(u+v)}\ du\ dv.$$

For this integral, the variables are to be changed from $(u, v)$ to $(u, t)$ so that $v = t - u$.

According to this video (~at 25:00), the result is

$$\int_0^\infty \int_0^t f(u)\ g(t - u) e^{-st}\ du\ dt.$$

The integrand is found easily, but what about the limits? In the video Prof. Mattuck gives a geometric argument, but I wonder how to the limits can be found in a more systematic way, like in the standard substitution rule

$$\int_{g(a)}^{g(b)} f(x)\ dx = \int_a^b f(g(t)) g'(t)\ dt.$$

In particular, where does the $t$ in the upper limit of the inner integral come from?

share|improve this question

2 Answers 2

up vote 2 down vote accepted

Using Fubini in a generous way we can argue as follows: The given double integral can be written as $$J:=\int_0^\infty \left( f(u)e^{-s u}\int_0^\infty g(v)e^{-sv}\ dv\right)\ du\ .$$ The substitution $v:=t-u$ $(u\leq t<\infty)$ transforms the inner integral into $$\int_u^\infty g(t-u) e^{s(u-t)}\ dt\ ,$$ and using Fubini again we obtain $$J=\int_0^\infty\int_u^\infty f(u)g(t-u) e^{-st} dt\ du=\int_B f(u)g(t-u) e^{-st} {\rm d}(u,t)\ ,$$ where $B$ is the the domain $$B:=\{(u,t)\ |\ u\geq 0,\ t\geq u\}=\{(u,t)\ |\ t\geq 0,\ 0\leq u\leq t\}\ .$$ (Note that you need some "geometry" in order to verify this.) Using Fubini with respect to the second representation of $B$, i.e., making $u$ the inner variable, we get $$J=\int_0^\infty\int_0^u f(u)g(t-u) e^{-st} du\ dt\ ,$$ as claimed by Prof. Mattuck.

A second way to arrive at the same result is the following:

(As the given integral is over an unbounded domain we have to be a little careful.)

We are told to replace the given independent variables $(u,v)$ by new variables $(x,t)$ (here $x$ is later to be renamed by $u$), using the formulas $${\bf w}:\quad(x,t)\mapsto \cases{u:= x\cr v:=t-x\cr}\ .$$

enter image description here

In this way the triangle $\Delta:=\{(x,t)\ |\ 0\leq t\leq T,\ 0\leq x\leq t\}$ in the $(x,t)$-plane is mapped onto the triangle $\Delta':=\{(u,v)\ |\ u\geq 0,\ v\geq0,\ u+v\leq T\}$ in the $(u,v)$-plane. (One can verify this by checking where the vertices go.) The Jacobian of this map is of absolute value $1$. Therefore one has $$\eqalign{\int\nolimits_{\Delta'} f(u)g(v)e^{-s(u+v)}\ {\rm d}(u,v)&= \int\nolimits_\Delta f(x)g(t-x)e^{-s\,t}\ {\rm d}(x,t)\cr &=\int_0^T e^{-st} \int_0^t f(x)g(t-x)\ dx\ dt\ .\cr}$$ On the right hand side the outer integration is with respect to the variable $t$, and the inner integration is over segments $t={\rm const.}$ parallel to the $x$-axis. (At the end one may replace the letter $x$ with $u$, if so desired.)

You will now have to check whether the assumptions made about $f$ and $g$ allow letting $T\to\infty$ in the last formula. If yes, you arrive at Prof. Mattuck's claim.

share|improve this answer
    
Thanks for your answer and the nice picture! What I find a bit hard to understand is how to come up with the reasoning about the triangles... by what rationale do you get from the double integral to the triangles? –  koletenbert Nov 6 '12 at 10:37
    
One more thought: I think the main point of my question is how to change variables for a double integral (improper or not). I was under the impression that there exists a simple substition formula (like in the single integral case), but it seems the "general" way to do it is to change it to a surface integral (thereby introducing geometric reasoning)... is that correct? –  koletenbert Nov 6 '12 at 10:44
    
@koletenbert: See my edit. –  Christian Blatter Nov 6 '12 at 11:34
    
Thanks! I like the Fubini version, that makes it clearer (to me, at least ;-)) –  koletenbert Nov 6 '12 at 22:58

$\int_0^\infty \int_0^\infty f(u)\ g(v) e^{-s(u+v)}\ du\ dv$=$\int_0^\infty f(u)e^{-su}du\int_0^\infty\ g(v) e^{-sv}\ dv$ then you can consider the Laplace transformation.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.